Symposium 2: Ubiquitous Learning: An Agenda for Educational Transformation - Cope, Bill; Kalantzis , Mary (Proceedings of the International Conference on Networked Learning, 2008)
Ubiquitous learning is a new educational paradigm made possible in part by the affordances of digital media. This paper sets out to explore the dimensions of this proposition. We can use new technologies to do learn old things in old ways. We can set up the ubiquitous computing devices in our contemporary world to do old-fashioned didactic teaching: the teacher or publisher puts content into a learning management system; the learner works through the content step by step; the learner does a test at the end and gets a mark which says they have passed or failed. We can use computers to recreate traditional, transmission pedagogies which anticipate a mimetic relationship to knowledge—absorb the theories, the practice formulae, the facts, the greats, the canon, the socio-moral truths that others have deemed will be good for you. There are some differences, to be sure—the image of the solar system in the old science textbook stays still but the planets move around the sun in the digital ‘learning object’—but the learner’s relationship to knowledge and the processes of pedagogy have not changed in any significant way (Kalantzis 2006; Kalantzis and Cope 2008). The emergence of ubiquitous computing creates new conditions for all working as education professionals and learning as students. The key is not the logic or technical specifications of the machines. Rather it is the new ways in which meaning is created, stored, delivered and accessed. This, we believe, will change the educational world in some fundamental ways—and also allow some older but good and disappointingly neglected educational ideas to work at last and work widely. The journey of ubiquitous learning is only just beginning. Along that journey. we need to develop breakthrough practices and technologies that allow us to reconceive and rebuild the content. procedures and human relationships of teaching and learning. In this paper, we suggest seven moves which are characteristic of ubiquitous learning. Each explores and exploits the potentials of ubiquitous computing. None, however, is a pedagogical thought or social agenda that is new to the era of ubiquitous computing. The only difference today is that there is now no practical reason not to make each of these moves. The affordances are there, and if we can, perhaps we should. And when we do, we may discover that a new educational paradigm begins to emerge. And as new paradigms emerge, we might find they take a leading role on technological innovation.